2011
DOI: 10.1590/s0100-84042011000400002
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporinas: de canais de água a transportadores multifuncionais em plantas

Abstract: -(Aquaporins: from water channels to multifunctional transporters in plants). From the functional identification of the first plant aquaporin, in 1993, up to today, a lot of information about the structure, location and function of different members of this multigene family of membrane proteins was provided by the scientific community. Initially regarded as "simple water channels", the aquaporins have been shown to transport gases and small neutral solutes such as glycerol, urea and silicon, transforming the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 91 publications
1
2
0
1
Order By: Relevance
“…An evaluation of these results confirms that particularly in our study the drop in the germination of seeds treated with 10 -3 M HgCl 2 was caused by lower seed hydration and not by possible oxidative stress, as some authors suggest (Willigen et al 2006;Gaspar 2011).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…An evaluation of these results confirms that particularly in our study the drop in the germination of seeds treated with 10 -3 M HgCl 2 was caused by lower seed hydration and not by possible oxidative stress, as some authors suggest (Willigen et al 2006;Gaspar 2011).…”
Section: Discussionsupporting
confidence: 91%
“…Some authors have discussed the potentially toxic side effects of mercury on plant metabolism (Willigen et al 2006;Gaspar 2011) and, for this reason, it is important to study the possible oxidative stress caused by this metal. It can be done by quantifying the activity of the main reactive oxygen species scavengers, such as superoxide dismutase (SOD), catalase (CAT), and peroxidases (POX).…”
Section: Introductionmentioning
confidence: 99%
“…Aquaporins (water channel proteins) are involved with the membrane transport of gases, solutes and ions, and their genes are found in every plant organ and tissue. These proteins are essential for water and nutrient uptake by roots, photosynthesis, transpiration and adaptation to environment-related stresses (Gaspar, 2011). Xu et al (2014) identified a plasma membrane aquaporin gene in the banana plant that induces drought tolerance by reducing the membrane damage, improving the ionic distribution by maintaining the osmotic adjustment with a high cytosolic K + /Na + ratio, and downregulating genes responsive to ABA, thereby increasing the plant survival rate.…”
Section: Resultsmentioning
confidence: 99%
“…A sua ação está na regulação do transporte de água durante a embebição, crescimento embrionário e protusão da radícula (GAO et al, 1999;GASPAR, 2011).…”
Section: Aminoácidos Atenuadores De Estressesunclassified